Consistência na indexação em bibliotecas universitárias brasileiras - Gil Leiva, Isidoro (2008)
The aim of this paper is to evaluate the consistency indexes among 30 Brazilian university libraries from the south and south-east regions through a specific mathematical formula. It was selected a sample of 30 university libraries that, according to the information in their official sites, have a collection consisted of more than 100.000 copies and allow the search into the on-line catalog. Searches were carried out in every university by means of their sites, requesting books that contained a certain word in its title and were printed in a certain year. The response was a list of available titles in the library, from which we chose at random a title and asked to visualize the complete record to verify the existence of a given subject. This procedure was repeated until we found the same title in five libraries with the chosen subjects. The result is 10 trials, each one consisting of one figure and one table showing the selected libraries, the subjects, the documentary languages (tools) and the consistency indexes “relaxed” and “rigid”. These trials show great discrepancy between the values of consistency indexes with intervals between 73,3% to 34,4% in the “relaxed” index, and between 60% and 9,6% in the “rigid” one. It was revealed that the coincidence in determining the subjects is not too high remaining below 39%. It is concluded that the difference between the consistency indexes may be due to factors as: incompatibility among documentary languages; lack of updating of these languages so as to follow the knowledge evolution; absence of a well-defined indexing policy with guidelines clearly established. Procedures of indexing followed by indexers could contribute to the consistency index to be bigger in percentage, since there would be parameters for the indexing process.